Teflon-buttressed sutures plus pericardium patch repair left ventricular rupture caused by radiofrequency catheter ablation: A case report. Issue 38 (September 2016) - Cao, Hao; Zhang, Qi; He, Yanzhong; Feng, Xiaodong; Liu, Zhongmin
Abstract: Background: Cardiac rupture often occurs after myocardial infarction or chest trauma with a high mortality rate. However, left ventricular rupture caused by radiofrequency catheter ablation (RFCA) is extremely rare. Methods: We describe a case of a 61-year-old male who survived from left ventricular rupture caused by a RFCA procedure for frequent ventricular premature contractions. Surgical exploration with cardiopulmonary bypass (CPB) was performed when the signs of cardiac tamponade developed 7 hours after the ablation surgery. Results: Teflon-buttressed sutures of the tear in the left ventricular posterolateral wall and pericardium patch applied to the contusion region on the wall repaired the rupture safely and effectively. Conclusion: Timely surgical intervention under CPB facilitated the survival of the patient. Teflon-buttressed sutures plus pericardium patch achieved the successful repair of the rupture.